The Determinants Of Customer Loyalty In The Financial Digital Industry: Bank-Based And Fintech-Based Qris Providers In Indonesia - Titania Permata Putri; Atik Aprianingsih (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The Indonesian digital financial system has been transformed through the Quick Response Code Indonesian Standard (QRIS), which has resulted in a homogenized environment with low switching costs. This study examines the factors that evenly contribute to customer loyalty of bank-based and fintech-based QRIS service providers through the Stimulus–Organism–Response (S-O-R) model. A quantitative method has been used in this study whereby the data was collected from 501 active QRIS users (296 from banks and 205 from fintechs). The findings indicate that Perceived Value has the strongest relative impact contribution to both groups. Contrary to previous findings, the findings of this study indicate that Trust acted as a hygiene factor without direct significant influence in this homogenized market environment. This study refutes the dominance of trust in the direct determination of customer loyalty in homogenized digital markets and has a bifurcated strategic roadmap.